Computing the Betti table of a monomial ideal: A reduction algorithm. (July 2018) - Torrente, Maria-Laura; Varbaro, Matteo
Abstract: In this paper we develop a new technique to compute the Betti table of a monomial ideal. We present a prototype implementation of the resulting algorithm and we perform some numerical experiments. As a major byproduct, we also prove new constraints on the shape of the possible Betti tables of a monomial ideal.